2014
DOI: 10.1186/ar4571
|View full text |Cite
|
Sign up to set email alerts
|

B cell subsets and dysfunction of regulatory B cells in IgG4-related diseases and primary Sjögren’s syndrome: the similarities and differences

Abstract: IntroductionIgG4-related disease (IgG4-RD) is a multisystem-involved autoimmune disease. Abnormally activated and differentiated B cells may play important roles. Regulatory B cells (Breg) are newly defined B cell subgroups with immunosuppressive functions. In this study, we investigated the differences of B cell subsets, the expressions of co-stimulatory molecules on B cells, and the function of Breg cells in patients with IgG4-RD, primary Sjögren’s syndrome (pSS) as well as in healthy controls (HC).MethodsNe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
82
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(86 citation statements)
references
References 36 publications
(41 reference statements)
4
82
0
Order By: Relevance
“…This factor is known to regulate the maturation and survival of B cells and mediate CD40 ligandindependent antibody production and induction of IgG4 class switching in the presence of IL-4 (18,19). Studies have shown that serum concentrations of BAFF and its homolog APRIL (a proliferation-inducing ligand) were significantly higher in patients with IgG4-RD than in healthy individuals (20,21) and that serum BAFF levels decrease following therapy (20). Serum BAFF levels have also been associated with the presence of cryoglobulins among HCV infected patients (22) and there have been reports of the effectiveness of a BAFF blockade in patients with cryoglobulinemic vasculitis associated with SLE (23) and Sjögren's syndrome (24).…”
Section: Discussionmentioning
confidence: 99%
“…This factor is known to regulate the maturation and survival of B cells and mediate CD40 ligandindependent antibody production and induction of IgG4 class switching in the presence of IL-4 (18,19). Studies have shown that serum concentrations of BAFF and its homolog APRIL (a proliferation-inducing ligand) were significantly higher in patients with IgG4-RD than in healthy individuals (20,21) and that serum BAFF levels decrease following therapy (20). Serum BAFF levels have also been associated with the presence of cryoglobulins among HCV infected patients (22) and there have been reports of the effectiveness of a BAFF blockade in patients with cryoglobulinemic vasculitis associated with SLE (23) and Sjögren's syndrome (24).…”
Section: Discussionmentioning
confidence: 99%
“…Detlefsen et al [40] reported that PDGF-BB expression was found by immunohistochemical staining in myofibroblasts and epithelial cells in AIP. In patients with IgG4-related diseases, increased expression of IL-4, IL-6 and IL-10 has been reported [41]. Obviously, further studies recruiting a large number of patients are required to clarify the cytokine profiles in AIP and their utility as AIP-specific biomarkers.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that CD19 + CD24 high CD38 high immature Bregs increase reactively to suppress disease activity, which is consistent with the hypothesis that CD19 + CD24 high CD27 + B10 cells might be involved in the development of type 1 AIP. Lin et al (2014) explored the relationship of Bregs in IgG4-RD in patients with IgG4-RD diagnosed according to comprehensive IgG4-RD diagnostic criteria established in 2011. Compared to patients with SS and healthy controls, IgG4-RD patients had a lower frequency of peripheral CD19 + CD24 hi CD38 hi immature Bregs.…”
Section: Bregs In Igg4-rdmentioning
confidence: 99%